FORMING and SIMULATION of stochastic processes with desired properties of trajectories - A. V. Ausiannikau; V. M. Kozel (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The necessary theoretical knowledge for the creation and simulation of stochastic processes with desired properties of trajectories is shown. These properties include: passage of the trajectory through a set process milestones (areas), the formation of the dynamics of the process in view of a given stationary probability density, determination of process parameters on the basis of a predetermined length and duration of the trajectory.